Other voices in the adventure expedition assemblage. Issue 3 (27th May 2022) - Kennedy, Suzanne; MacPhail, Ann; Varley, Peter
ABSTRACT: Necessitating both temporal and spatial separateness from everydayness, the outdoor expedition setting offers adventurers a uniquely discrete social context and simplified way of living in the natural world. Typically exploratory in character and risky in nature, the expedition phenomenon has been positioned in the literature as a particularly masculinized space, with a discourse built around the physicality and toughness that is required to succeed in the field. This paper explores women's perspectives on such a setting. It sheds light on how a small group of experienced sea kayakers prepared for and experienced the outdoor world of expedition living in terms of their expeditional readiness, ability to animate the setting, and their willingness to immerse in the natural world. It considers how insights from such deeply immersive experiences in the other-than-human world can be translated in more everyday terms for those less accustomed to outdoor leisure and recreation.